The Effect of Competence, Communication & Motivation on Employee Performance in People’s Welfare Regional Secretariat of Padang City, Indonesia - Jamilus, Jamilus; Heryanto, Heryanto (Archives of Business Research, 2019)
The purpose of this study is to determine the effect of competence, communication, motivation and employees performance the People's Welfare Regional Secretariat of Padang City. This research is motivated by low employee performance and low competence and employee communication in the execution of work. Research method with a quantitative approach with path analysis method. Data collection techniques with questionnaires, observation and interviews. The respondents of this study are 49 employees at the People's Welfare Regional Secretariat of Padang City. The sample method uses census sampling method wherein the entire population in this study is used as the research sample. Hypothesis testing is calculated by IBM Statistical Package for Social Science (SPSS) program version 21.0. The results of this study found that competence does not have a significant effect on motivation, communication does not have a significant effect on motivation, motivation does not have a significant effect on performance, competence has a significant effect on performance, communication has a significant effect on performance, indirectly competence through motivation has no significant effect on performance and indirectly communication through motivation has a significant influence on employee performance in the People's Welfare Regional Secretariat of Padang City, Indonesia.